Anaerobic Digestion of Duckweed Used to Remediate Water Contaminated with Zinc and Ammonium - Yan Zhang; Xinmin Zhan; Artin Hatzikioseyian; Piet Nicolaas Luc Lens (Applied Sciences)
This study presents an integrated approach for the remediation of zinc- and ammonium-contaminated water using duckweed, followed by the valorization of the harvested biomass through anaerobic digestion for biogas production. Duckweed was cultured with various initial concentrations of zinc (Zn, 0 mg/L, 2.5 mg/L, and 5 mg/L) and ammonium (NH4+-N, 0 mg/L, 20 mg/L, and 40 mg/L). Subsequently, duckweed was subjected to chemical pretreatment with sulfuric acid and the obtained residual solid and liquid fractions were evaluated as substrates for methane production. The liquid fraction consistently yielded higher methane production compared to the solid fraction. However, when duckweed was grown in zinc- and ammonium-rich conditions (2.5 or 5.0 mg/L Zn and 20 mg/L NH4+-N), methane production from the liquid hydrolysate was significantly reduced (120.90 ± 12.03 mL/g COD and 129.82 ± 10.65 mL/g COD, respectively) compared to the control duckweed (201.67 ± 5.72 mL/g COD). The lowest methane yields were observed for duckweed grown solely in zinc (111.32 ± 5.72 and 99.88 ± 10.49 mL/g COD for 2.5 and 5.0 mg/L Zn, respectively), attributed to the inhibitory effect of high dissolved zinc concentrations in the liquid fraction. The applicability of this integrated system is particularly relevant for the agricultural and industrial sectors, where wastewater streams are often co-contaminated with nutrients and trace metals. By demonstrating that acid-pretreated, zinc-rich duckweed biomass can be used for biogas production—provided that process conditions are optimized to mitigate metal inhibition and acidification—this study provides actionable strategies for developing circular, sustainable wastewater treatment systems. The approach not only maximizes pollutant removal and resource recovery, but also addresses environmental safety concerns associated with residual metals in the digestate.